Roughness of ZnS : Pr,Ce/Ta2O5 interface and its effects on electrical performance of alternating current thin-film electroluminescent devices - Lee, YH; Kim, YS; Ju, BK; Oh, MH (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 1999)
Roughness effects of neighboring dielectrics on electrical characteristics of thin-film electroluminescent devices were investigated in order to improve the understanding of physics for the devices. Atomic force microscopy analysis reveal that thicker bottom layer of Ta2O5 shows rougher surface resulting in the rougher surface of ZnS:Pr,Ce layer, It can be easily seen that the de leakage current increases rapidly with increase of surface roughness Furthermore, it is notable that the initiation field of Poole-Frenkel current conduction is lowered by increasing surface roughness of Ta2O5 thin film. Internal charge-phosphor field (Q(int) - F-p) analysis and capacitance-ac voltage (C-V) analysis for ITO-Ta2O5-ZnS: Pr,Ce-Al and ITO-Ta2O5ZnS:Pr,Ce-Ta2O5-Al show that the steady state phosphor field is smaller and C-V curve in transition region is less steep with increase of root-mean-square roughness between lower dielectric and phosphor layer in the alternating current thin-film electroluminescent (ACTFEL) devices. Therefore, we conclude that interface roughness is one of the physical factors to change the electrical performance of ACTFEL device.